Fairness Deliberations and Fair Allocations in Symmetric and Asymmetric Bargaining–An Experimental Study on Group Decisions in Germany and China - Heike Hennig-Schmidt; Zhuyu Li; Gari Walkowitz (Group Decision and Negotiation, 2024)
The study's primary focus is on examining fairness deliberations of bargainers in Germany and in China under symmetric and asymmetric bargaining power to understand whether they incorporate fairness into their decision process and, if so, how this affects bargaining outcomes. To this end, we conducted an incentivized ultimatum bargaining experiment with symmetric and asymmetric outside options. Groups ( N 0.167em=0.167em142) of three persons interact as proposers and responders in dyads and decide simultaneously on their offer or which offers to accept or reject. Communication between parties is inhibited. We videotaped in-group discussions; the resulting transcripts were text analyzed by eliciting whether groups make fairness an issue, which fairness norms they discuss, and whether they use fairness-related perspective-taking to overcome the communication constraint. We find that asymmetry of bargaining power in favor of the proposer leads to lower offers relative to the symmetric situation. Not all groups make fairness an issue, and fairness deliberations alone have no significant impact on offers. However, when associated with the equal-payoff norm, and in Chinese groups in particular, discussing fairness increases offers in symmetric but also in asymmetric situations, in which other fairness norms could have been applied, too. Fairness-related perspective-taking is used by German and Chinese groups and is associated with higher offers in the former. Our study makes an epistemological and related methodological contribution: a possibly biased interpretation of bargaining outcomes can be mitigated if information on decision processes and underlying mechanisms were available.
Keywords: C78; C81; C91; C92; O53; O57; 650; Group decision-making; Fairness and equality; Perspective-taking; Focal points; Tacit bargaining; Ultimatum game; Video experiments; Content analysis